Um corpo para o trágico: Corporeidade e Erotismo na tragédia Fedra de Sêneca - Silva, Leyla Thays Brito da (2016)
This work dedicates itself to the study of the Seneca’s Phaedra a tragedy written by the Latin poet in the 1st century BC. The research has as its investigative urge the identification of symbolic as the core of the play’s tragic plot. Despite the poet’s education in Stoicism and his various doctrinal dramatic productions, we assume that Phaedra features poetic and dramatic components that evoke the possibility of a different reading. Against a critical tradition that underestimated the ultra-pathetic and appalling components of Seneca’s tragic work, we try to find in these aesthetic features Phaedra’s poetic and dramatic structure. Therefore, we consider that the mythicsymbolic basis, expressed through raw, passionate and violent images, reveals a cohesion still not seen by critics. Thus, we propose that the relationship between bodyeroticism-death and its poetization through symbolic signs constitute the fundamental elements of the play’s tragic content and structure. In this sense, this research identifies the tragic in the characters’ corporeality. Consequently, the term corporeality, as a totality of the human condition in which body and mind are involved in the development of knowledge appears as a fundamental theoretical concept. The symbol as a sign that emerges from the body, as proposed by the anthropologist Gilbert Durand, serves to recognize that the Seneca’s Phaedra implies in its composition uninterrupted drama between love and death affecting the body and the whole of human existence.